2021
DOI: 10.3390/met11111777
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Vanadium (V) Oxyanions by a Magnetic Macroporous Copolymer Nanocomposite Sorbent

Abstract: An amino-functionalized magnetic macroporous copolymer of glycidyl methacrylate (GM) and ethylene glycol (E) dimethacrylate (m-poly(GME)-deta) was synthesized, fully characterized, and used to investigate the adsorption of vanadium (V) oxyanions from aqueous solutions (Ci = 0.5 mM) in a batch system at room temperature (298 K). Pseudo-first-order (PFO), pseudo-second-order (PSO), Elovich, and intra-particle diffusion (IPD) models were used to analyze the kinetic data. The study showed that sorption is rapid, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The magnetic polymer sample functionalized with diethylenetriamine (Fe 3 O 4 @APTMS/PGME-deta) was porous with a pore diameter corresponding to half of the pore volume of 286 nm and a specific pore area value of 37 m 2 /g, as determined by mercury porosimetry [ 21 ]. The sample Fe 3 O 4 @APTMS/PGME-deta was also fully characterized using SEM, TEM, ATR-FTIR, XRD, and SQUID magnetometry.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The magnetic polymer sample functionalized with diethylenetriamine (Fe 3 O 4 @APTMS/PGME-deta) was porous with a pore diameter corresponding to half of the pore volume of 286 nm and a specific pore area value of 37 m 2 /g, as determined by mercury porosimetry [ 21 ]. The sample Fe 3 O 4 @APTMS/PGME-deta was also fully characterized using SEM, TEM, ATR-FTIR, XRD, and SQUID magnetometry.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous works demonstrated that calculating the coordination bond energy for the chemisorption of metal ions on the polymer gives excellent agreement with the experimentally determined maximum sorption capacities [ 27 , 67 ]. Quantum chemical modeling of physisorption and calculation of the energy of non-covalent binding proved to help explain the binding mechanism of oxyanions to the polymer and the affinity of individual oxyanions for the polymer [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of extensive research, Jovanović et al developed GMA-based polymeric sorbents with adjustable porosity parameters by varying the type and the amount of aliphatic alcohol and crosslinking monomer in the reaction mixture [23]. A plethora of amino-functionalized porous polymers and composites were used as heavy and precious metal sorbents, with the possibility to coordinate gold and platinum metals or bind them as chloro complexes as basic ion exchangers, depending on pH [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%